Menjadi Eksportir Baru Melalui Studi Independen Di PT Lacorre Loka Maya Bertema Vokasi Digital Ekspor Fesyen - Kevin Adi Septian; Rahman Amrullah Suwaidi (Pakis Journal Institute, 2024)
The Internship and Independent Program provides a space for students to gain experience to know and gain understand the professional world and prepare a professional workforce. PT LaCorre Loka Maya is a partner working with the MSIB program. PT LaCorre Loka Maya is a digitally oriented learning and training institution under Arrbey and collaborates with Sekolah Ekspor to provide digital training for exporting commodities within the country. PT LaCorre Loka Maya provides learning in accordance with current developments with aim of producing young exporter who can develop local product that have high sales potential and market value abroad. Students are expected to help UMKM products to compete with foreign products in the international market. In the education and training carried out by PT LaCorre Loka Maya, students are asked to carry out project development where this project is the testing material in this education and training. The project developed is a Batik patterned tie that has the product name TIEK. Batik patterned fashion has its own value that reflects one of the forms of art and culture that has been developed by the Indonesian people for a long time. Batik is often produced in the form of t shirt, shirts, pants, sarongs, and more. But ties in the form of batik motifs are still rare. Therefore, the fashion potential of batik patterned ties will open a new market share in the fashion business of the domestic and international markets.